Answer:
40x² + 65x + 25
Explanation:
We will just multiply each term from the first bracket by each term from the second and then combine like terms to get the final expression.
This would be done as follows:
(5x + 5)(8x + 5)
5x(8x) + 5x(5) + 5(8x) + 5(5)
40x² + 25x + 40x + 25
40x² + 65x + 25
Hope this helps :)
Hey there! :D
That's like saying:
-2*-2*-2
-2*-2=4
4*-2= 8
"D" -8 <== the answer
I hope this helps!
~kaikers
You can’t? I mean like adding 100 at a time or-
It equals 5/6 And the decimal form is 0.8333 and so on